2021
DOI: 10.1097/olq.0000000000001526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Check It: A Novel Community-Based Chlamydia Screening and Expedited Treatment Program for Young Black Men

Abstract: Objectives: This study aimed to estimate the impact of the Check It program, a novel community-based chlamydia seek, test, and treat program for young Black men who have sex with women, on test positivity rates for chlamydia in young Black women. Methods:We used a synthetic control model to compare chlamydia test positivity rates in Orleans Parish (intervention site) with other similar parishes (control sites) in Louisiana. We estimated a model that used all other parishes as potential contributors to a synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The Check It study is a novel, bundled, community-based seek, test, and treat Ct screening program for 15- to 26-year-old Black men in New Orleans who have sex with women [ 10 ]. Check It was designed with the purpose of determining if community-based Ct screening of young Black men ages 15–26 in New Orleans could both address barriers to Ct screening and treatment in this group and decrease rates of Ct in young women in New Orleans [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Check It study is a novel, bundled, community-based seek, test, and treat Ct screening program for 15- to 26-year-old Black men in New Orleans who have sex with women [ 10 ]. Check It was designed with the purpose of determining if community-based Ct screening of young Black men ages 15–26 in New Orleans could both address barriers to Ct screening and treatment in this group and decrease rates of Ct in young women in New Orleans [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The program has been evaluated using agent-based modeling and it was found that each man screened prevented approximately 0.062 cases in men and 0.204 cases of chlamydia in women [ 16 ]. A study using Medicaid claims found the program resulted in a 1.69% decline in claims related to chlamydia positivity in the first year of its operation [ 17 ].…”
mentioning
confidence: 99%